Between Obedience and Resistance: A Futuristic Fiqh Approach to the 2025 House of Representatives Demonstration - Muhammad Alwi; Syahrizal Syahrizal (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
The 2025 DPR demonstration was one of the biggest political events in Indonesia, triggered by controversial policies that caused public unrest and widespread rejection. This phenomenon highlights the dilemma between the obligation to obey the authorities and the urge to resist policies that are considered unjust. Previous studies in classical fiqh tend to emphasise the principle of obedience, while contemporary fiqh discourse has not fully elaborated on the legitimacy of political resistance in the modern context. This study aims to analyse the 2025 DPR demonstrations through a futuristic fiqh perspective, focusing on the ethics of obedience, the legitimacy of resistance, and maqāṣid al-syarī‘ah as an ethical framework. The research method uses a normative-philosophical qualitative approach with critical discourse analysis (CDA), based on classical and contemporary fiqh literature, futuristic fiqh theory, official documents of the 2025 DPR, and secondary data in the form of news and public opinion on social media. The results of the study show that although classical fiqh emphasises obedience to the authorities, futuristic fiqh opens up space for peaceful, moral, and constructive political resistance. This study affirms the contribution of futuristic fiqh as a new approach in Islamic political ethics, which is more responsive to the dynamics of modern society and can be the basis for the development of regulations and socio-political advocacy strategies in the future